The Sherlock Holmes feature film collection [videorecording (DVD)] - Hammond, Peter, 1923-2011; Brett, Jeremy, 1933-1995; Hardwicke, Edward; Doyle, Arthur Conan, 1859-1930 (MPI Home Video, 1993)
Dramatization of a story by Sir Arthur Conan Doyle. The most eligible bachelor in London, Lord St. Simon, has just married a wealthy American woman. The young couple's wedding day turns to tragedy when an unwelcome guest arrives at the wedding breakfast and the bride disappears. Sherlock Holmes is plagued with terrible nightmares, which cause him to regard the plight of Lord St. Simon with contempt. Will Holmes take the case?